The Importance of Studying English in Higher Education for SEN: Pathways to Social Mobility and Personal Development - Antonia Tefa; Engelbertus Kase; Chamelya Sene (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to examine the importance of studying English in higher education for students with Special Educational Needs (SEN), focusing on its role in promoting social mobility and personal development. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving ten SEN students enrolled in English courses at a private university in East Nusa Tenggara. The findings reveal that English proficiency serves as a crucial gateway to economic opportunities, enabling students with SEN to obtain academic qualifications, enhance employability, and prepare for transitions into an increasingly global and digital labor market. English study also contributes to long-term professional resilience by granting access to international networks, remote work opportunities, and global discourses on disability rights. Beyond economic benefits, English learning fosters intellectual growth, self-confidence, autonomy, and the exploration of personal interests. It provides a platform for self-expression, social inclusion, and leadership development supported by inclusive teaching practices. Overall, the study concludes that English learning in higher education plays a transformative role in empowering students with SEN to overcome structural barriers, assert their academic identity, and participate fully as active and equal members of society.